Development of Arabic language teaching materials based on information technology for elementary schools - Kurniawan Djody; S. Suharsiwi; Muhyiddin Tohir Tamimi; B. Busahdiar; Fauzi Al-Mubarok (Research and Development in Education (RaDEn), 2024)
Arabic, as one of the most widely spoken languages globally, holds substantial cultural and economic importance, particularly in the context of Islamic studies and international relations. However, teaching Arabic in elementary schools often faces challenges, including a lack of engaging and effective teaching materials that cater to the diverse needs of young learners. The purpose of this research is to create a design for developing Arabic language teaching materials for elementary schools subject research SDIP Darum Musthofa. This type of research is research and development or what is usually called Research and Development (R&D) using the Borg and Gall development design model. This research produced a product in the form of draft Arabic language teaching materials for third-grade elementary schools. The design of this teaching material shows that the information technology-based Arabic language teaching material developed has a high level of feasibility. This is proven by the results of the design expert validity test showing a percentage of 96% with a very decent predicate, the content/material validity test reached 90% with a very good predicate and also the linguist validity test reached 89% with a very good predicate. The results of the field test on students were 32.7% who said they were very good and 65.5% who said they were good. Based on the test results. The supporting factors for this development are supporting technology, and students who are capable of technology, while the inhibiting factors are the limited media provided at school.